Five-Year Outcomes After Endovascular Treatment for Large Vessel Occlusion Stroke - Gong, Changxiong; Huang, Jiacheng; Kong, Weilin; Li, Fengli; Liu, Chang; Yang, Jie; Liu, Shuai; Qiu, Zhongming; Lin, Min; Guo, Zhangbao; Yan, Zhizhong; Huang, Xianjun; et al. (Frontiers in Neuroscience, 2022)
BACKGROUND: The long-term outcomes of acute large vessel occlusion in anterior circulation treated by endovascular treatment remains to be determined. The aim of this study was to assess the 5-year outcomes of patients with LVO who underwent EVT. METHODS: This study was an observational, nationwide registry of consecutive patients with acute LVO who received EVT in 28 comprehensive stroke centers in China. The primary outcome was the proportion of favorable outcome (mRS 0–2) at 5 years. Secondary outcomes included proportions of patients with excellent outcome (mRS 0–1), all-cause mortality and risk of stroke recurrence at 5 years. RESULTS: A total of 807 patients were included into the study and had 90-day follow-up data, 657 patients had 5-year follow-up data. At 90 days, 218 (27.0%) had an excellent outcome, 349 (43.2%) had a favorable functional outcome. 199 (24.7%) died. At 5 years, 190 (28.9%) had an excellent outcome, 261 (39.7%) had a favorable functional outcome, 317 (48.2%) died and 129 (28.2%) had stroke recurrence. Among available 269 patients who achieved functional independence at 90 days, 208 (77.3%) maintained favorable outcome, 19 (7.1%) had disability (mRS 3–5) and 42 (15.6%) died at 5 years. Furthermore, among available 189 patients with mRS 3-5 at 90 days, 53 (28.0%) patients achieved favorable functional outcome, 60 (31.7%) patients maintained unfavorable functional outcome and 76 (40.2%) patients died within 5 years. Multivariate analyses identified that younger age (odds ratio [OR]: 0.96; 95% CI, 0.93–0.99; P=0.009), lower mRS at 90 days (OR: 0.15; 95% CI, 0.10–0.23; P<0.001) and absence of stroke recurrence (OR: 0.001; 95% CI, 0.000–0.006; P<0.001) were significantly associated with favorable outcome at 5 years. Advanced age (OR: 1.06, 95% CI, 1.04–1.08; P<0.001), higher mRS at 90 days (OR: 0.84; 95% CI, 0.73–0.98; P=0.021) and atrial fibrillation (OR: 1.63; 95% CI, 1.02–2.60; P=0.04) were independent factors for stroke recurrence. CONCLUSIONS: Our results indicated that the beneficial effect of EVT in patients with acute LVO can be sustained during the course of at least 5 years. Reducing the risk of stroke recurrence by anticoagulation for atrial fibrillation may be a crucial strategy to improve long-term outcome.